2022
DOI: 10.1002/ijgo.14514
|View full text |Cite
|
Sign up to set email alerts
|

Women's mental health and climate change Part II: Socioeconomic stresses of climate change and eco‐anxiety for women and their children

Abstract: Climate change is a significant public health crisis that is both rooted in pre-existing inequitable socioeconomic and racial systems and will further worsen these social injustices. In the face of acute and slow-moving natural disasters, women, and particularly women of color, will be more susceptible to gender-based violence, displacement, and other socioeconomic stressors, all of which have adverse mental health outcomes. Among the social consequences of climate change, eco-anxiety resulting from these nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Across the world, women are more likely to suffer from mental illness following extreme weather events (Cruz et al, 2020). Mental health professionals use the term eco-anxiety to refer to the stress and grief many feel about the climate and environmental crisis (Rothschild & Haase, 2023). Women tend to be more susceptible to the development of eco-anxiety, depression, and posttraumatic stress disorders associated with CEC than men (Heeren et al, 2022).…”
Section: Climate and Environmental Changes Affect The Health Of Vulne...mentioning
confidence: 99%
“…Across the world, women are more likely to suffer from mental illness following extreme weather events (Cruz et al, 2020). Mental health professionals use the term eco-anxiety to refer to the stress and grief many feel about the climate and environmental crisis (Rothschild & Haase, 2023). Women tend to be more susceptible to the development of eco-anxiety, depression, and posttraumatic stress disorders associated with CEC than men (Heeren et al, 2022).…”
Section: Climate and Environmental Changes Affect The Health Of Vulne...mentioning
confidence: 99%
“…Climate‐related exposures can also increase risks of cancer 8 . Additionally, climate change‐induced ecological events, including drought and floods, will lead to greater displacement and violence, disproportionately affecting women's mental health, physical safety, and overall well‐being 9–11 . This also includes an increase in armed conflict over scarcer resources and displacement that will unequally burden women 12 …”
Section: Women Will Experience Greater And/or Unique Effects Globallymentioning
confidence: 99%
“…In addition, a study by Hu et al found that suicide rates rose by 1% for each 1°C increase on average monthly temperature 32 . Yet another study found that deviations from moderate temperatures and precipitation patterns systematically increase the risk of conflict, whether interpersonal, such as rape and domestic violence, or intergroup, like civil wars 33,34 . These studies serve to emphasize the importance of acknowledging and addressing the effect of heat on mental health.…”
Section: Introductionmentioning
confidence: 99%
“… 32 Yet another study found that deviations from moderate temperatures and precipitation patterns systematically increase the risk of conflict, whether interpersonal, such as rape and domestic violence, or intergroup, like civil wars. 33 , 34 These studies serve to emphasize the importance of acknowledging and addressing the effect of heat on mental health. With global temperatures projected to continue rising due to climate change, the relevance and urgency of this topic have become more important.…”
Section: Introductionmentioning
confidence: 99%